2000
DOI: 10.1093/her/15.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating `Safe in the Sun', a curriculum programme for primary schools

Abstract: Eleven schools in the south of England took part in a trial of 'Safe in the Sun', a curriculum programme for primary school aged pupils. Case study methodology and the 'draw and write' technique were combined to evaluate changes in pupils' perceptions of the effects of the sun on their skin. Teachers were free to use the materials, consisting of a teacher's handbook and video, as they wished. Pupils in all schools showed higher levels of awareness of sun-safety measures in post-intervention studies compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 11 publications
1
37
0
1
Order By: Relevance
“…This method has been used to explore children's views about a range of health topics, including HIV/AIDS, drugs, and skin cancer [14,18-20]. We used it to explore primary schoolchildren's perceptions of healthy and diseased eyes, things that keep eyes healthy and damage them, and what action to take in case of an eye injury.…”
Section: Methodsmentioning
confidence: 99%
“…This method has been used to explore children's views about a range of health topics, including HIV/AIDS, drugs, and skin cancer [14,18-20]. We used it to explore primary schoolchildren's perceptions of healthy and diseased eyes, things that keep eyes healthy and damage them, and what action to take in case of an eye injury.…”
Section: Methodsmentioning
confidence: 99%
“…Sería ideal institucionalizar un programa educativo escolar dedicado a este tema, dictado por los profesores, y que involucre a los padres, quienes tienen gran influencia en el comportamiento de los niños, para así lograr una mayor efectividad, tal como se ha demostrado en otros estudios (17)(18)(19).…”
Section: Discussionunclassified
“…Moreover, it has been demonstrated that the length of the intervention in sun education is associated with the duration of the effect (Hewitt et al, 2001). In contrast, multiunits presentation in which the sun protection message is repeated through long programmes over months and years induced improvements both in knowledge and children's behaviour (Ramstack et al, 1986;Girgis et al, 1993;Buller et al, 1996;Bastuji-Garin et al, 1999;McWhirter et al, 2000).…”
Section: Mean Increasementioning
confidence: 99%